Sierra Leone : Poverty Reduction Strategy Paper Preparation Status Report. (IMF Staff Country Reports; Country Report ;, 2005)
This paper examines Sierra Leone's Poverty Reduction Strategy Paper (PRSP) Preparation Status Report. The government of Sierra Leone submitted its last PRSP preparation status report to the Executive Boards of the IMF and the World Bank in June 2003. However, the projected completion date of December 2003 was missed owing to continuing administrative and technical difficulties as well as delays in accessing technical and financial assistance from key partners. A draft PRSP has been prepared and issued in August 2004 to all stakeholders for comments and suggestions.